Spatio-temporal differences and simulation studies of the carbon budget from fisheries in the northern marine economic circle of China - Jia, Dai; Liu, Xinyu; Guan, Xin; Guo, Jinfei; Zhang, Shuqi; Li, Haozheng; Jin, Yiyang; Sun, Jun (Frontiers in Marine Science, 2024)
With the proposal of dual carbon goals, enhancing carbon sinks and reducing carbon emissions has become a critical issue. Fisheries, as a component of agriculture, possess the dual attributes of being a “carbon sink” (biological carbon fixation) and a “carbon source” (the carbon emissions from fishing vessels). Therefore, it is necessary to assess the carbon sink and carbon emission levels of fisheries. The northern marine economic circle, which includes Liaoning, Hebei, Tianjin, and Shandong, is an important site for fisheries in China, characterized by abundant aquatic resources. However, a comprehensive assessment of the carbon budget for fisheries in this region is still unclear. This study calculated the carbon sinks, carbon emissions, and net carbon emissions associated with fisheries in the region from 2013 to 2020. Additionally, we used sensitivity analysis and scenario simulation to explore the factors influencing the net carbon emissions. The results revealed that the carbon budget of the northern marine economic circle was in a carbon deficit (the amount of carbon emissions was higher than that of carbon sinks) from 2013 to 2020. However, a downward trend in the net carbon emissions was observed, indicating the potential of achieving carbon neutrality. From the perspective of provinces, significant differences among provinces (cities) were found in terms of carbon sinks, carbon emissions, and net carbon emissions, with Shandong having the largest net carbon emissions. Furthermore, the production of clams and the use of seawater trawl net have a significant impact on the net carbon emissions. Increasing the production of clams while reducing the power of trawling operations can significantly decrease net carbon emissions. Based on these results, this study provides relevant suggestions to enhance the carbon sink capacity and decrease the carbon emissions of fisheries in the northern marine economic circle.